Charles Todd and the Overland Telegraph Line: A Book Review of “Mr Todd’s Marvel” - Holmes, Jim (Journal of Telecommunications and the Digital Economy, 2024)
Adam Courtenay, an Australian author and journalist completed Mr Todd’s Marvel: How one man telegraphed Australia to the modern world, a recent book on Charles Todd and the Overland Telegraph Line (OTL), in time for it to be published around the 150th anniversary of the completion of the historic project. Although the book concentrates on the immense task and challenges of building the OTL from Port Augusta to Palmerston (now called Darwin), it does provide a focus on the people that participated and, especially, on the special role of Charles Todd. This book review concludes that the book is a useful introduction to the subject, with occasional inclusions of information that might not be well known, and permits the reader easy access to the subject through its narrative style and generous spread of illustrations.However, the book does have limitations. It lacks an index and citations detailed enough to be followed up. For the reader who might wish to pursue particular issues or events, these limitations are frustrating indeed. Overall, it is for the general reader, rather than for those seeking to gain an even deeper understanding of the times, the project, and the major participants and their motivations.